TRADISI MANGAJI NAGARI KUNCIR KECAMATAN X KOTO DIATAS KABUPATEN SOLOK: KAJIAN SEMIOTIKA - Halid, Elan; Dwinitia, Suci; Yuniar, Lativa Raudhatul (Asosiasi dosen IDEBAHASA KEPRI, 2025)
Semiotic studies examine the study of signs and meanings. The Minangkabau people are one of the largest ethnic groups in Indonesia originating from the West Sumatra region and several surrounding areas, and are known for their unique culture, customs, and social systems. One of the Nagari in West Sumatra is Nagari Kuncir which has a tradition of mangaji samalam, tigo hari, seven hari, fourteen hari, fifty hari, and one hundred hari. The purpose of this study is to describe the Mangaji Tradition of Nagari Kuncir, X Koto Diatas District, Solok Regency: Semiotic Study. This type of research is qualitative with descriptive methods. The data are in the form of pillows, clothes, mattresses, prayer beads, umbrellas, sandals carried out in the mangaji procession. This study involved three informants, namely people who know the ins and outs of the mangaji tradition, namely the Family, Datuak, and Bundo Kanduang. Data collection techniques are in the form of field observations, interviewing informants, recording, noting the process in the mangaji tradition, and documenting the process in the mangaji tradition. The data analysis techniques are: re-reading all the collected data, marking by coding the data, classifying the data according to the table format, interpreting and analyzing the collected data based on semiotic components in the form of signs, symbols, emblems, and drawing conclusions. From the research, 27 data were found. The most frequently found data is in the tradition of reading the one hundred days of semiotic symbol components, amounting to eleven data.